THE IMPLEMENTATION OF A FLIPPED CLASSROOM IN FOREIGN LANGUAGE TEACHING - BASAL, Ahmet (The Turkish online journal of distance education TOJDE, 2015)
Alongside the rise of educational technology, many teachers have been taking gradual but innovative steps to redesign their teaching methods. For example, in flipped learning or a flipped classroom, students watch instructional videos outside the classroom and do assignments or engage in activities inside the classroom. Language teachers are one group of educators exploring the flipped classroom. In foreign language classes, such an approach may offer great benefits for both the teachers and students since classroom time can be applied to more interactive tasks. By extending classroom hours in this way, language teachers can focus on successfully addressing all subjects in the curriculum. The aim of this study is (a) to gain insights into the perceptions of prospective English language teachers at a state university in Turkey on flipped classrooms and (b) to introduce the implementation of a flipped classroom into an English language class. A total of 47 prospective English teachers participated in the study. Qualitative research design was used and data were collected via an open-ended question. Findings of the study indicated that pre-service English teachers had positive perceptions towards the use of the flipped classroom as an integral part of face-to-face courses. It can be concluded that flipped classroom was beneficial in terms of 4 categories based on the content analysis of the responses: learning at one's own pace, advance student preparation, overcoming the limitations of class time, increasing the participation in the classroom. The study also provides recommendations towards LMS integration into courses in other English language teaching departments and for implementing flipped classrooms in language teaching.